"A Success in Every Particular": British August First Celebrations in Canada and America and the Black Quest for Unblemished Commemorations, While Critiquing July Fourth, 1834–1861. Issue 4 (2nd October 2017) - Broyld, dann j.
ABSTRACT: British August First celebrations were an important day of the year for Blacks in North America. Elite and aspiring organizers attempted to use the holiday as a sight of excellence. Partakers understood they were watched closely during commemorations and that their slightest imperfections could be magnified to unreasonable proportions. Thereby, Blacks felt it was essential to present themselves in near "perfection" to prove that they could be "upstanding citizens." This article asserts that the standard of outright excellence Blacks attempted to execute on August First was neither achievable nor performed by Whites at celebrations like July Fourth. While Whites could be the notorious offenders of uncivilized and imperfect behavior, First celebrations were to be as the Liberator proclaimed an "array of virtue, loveliness, moral heroism, and true piety." In all, when Blacks utilized the power to assemble, it was viewed more as a potential site of lawlessness and subversion, despite their efforts.